2020
DOI: 10.4018/978-1-5225-9750-6.ch010
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Analytics in the Healthcare Industry

Abstract: Big Data has changed the way we manage, analyze and impact the data information in any industry. A champion among the most promising zones where it will, in general, be associated with takeoff progress is therapeutic medicinal administrations. Administration examinations can diminish costs of treatment, foresee flare-ups of pestilences, keep up a key separation from preventable diseases and improve individual fulfillment overall. The chapter depicts the beginning field of a huge information investigation in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…SVM produced accuracy with Weka tool. In (Acharjya, 2016;Varatharajan and Varatharajan, 2020;Sampathkumar-Rastogi, et al, 2020), Chowdhary et al utilized mammography images for the detection of breast cancer using intuitive fuzzy histogram magnification approach thereby data was processed and image quality was improved (Kelly-Dean, et al, 2010):…”
Section: Related Workmentioning
confidence: 99%
“…SVM produced accuracy with Weka tool. In (Acharjya, 2016;Varatharajan and Varatharajan, 2020;Sampathkumar-Rastogi, et al, 2020), Chowdhary et al utilized mammography images for the detection of breast cancer using intuitive fuzzy histogram magnification approach thereby data was processed and image quality was improved (Kelly-Dean, et al, 2010):…”
Section: Related Workmentioning
confidence: 99%
“…Patil and Vohra (2021) edited a handbook of research that focuses on healthcare applications of data science and analytics. Varatharajan et al (2020) discussed an in-depth study of big data analytics in the healthcare industry by analyzing healthcare applications using machine learning. Varatharajan et al (2020) discussed the need for big data analytics in the healthcare ecosystem with personal health records, electronic health records, health information exchange, and national and international health analytics.…”
Section: Introductionmentioning
confidence: 99%
“…Varatharajan et al (2020) presented an in-depth discussion of streaming healthcare data using data analytics with stages that are summarized in Table 2. Varatharajan et al (2020) also presented several big data platforms and big data tools that are each discussed in more depth with others in Segall & Gao's (2020) work and in a chapter by Segall (2020b) pertaining to open-source software for the statistical analysis of big data. Varatharjan et al (2020) showed that the three most important roles of big data analytics in healthcare are cost reduction, faster & better decision making, and new products and services.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations